1971
DOI: 10.1103/physrevlett.26.737
|View full text |Cite
|
Sign up to set email alerts
|

1s3dExcitation of Atomic Hydrogen by Electron and Proton Impact

Abstract: der, Phys. Rev. Lett. 25, 988 {1970). P. Bertoncini and A. Wahl, Phys. Rev. Lett. 25, 991 (1970).The Glauber approximation has been applied to calculate the total and the differential cross sections of Is-% excitation of the hydrogen atom by electron and proton impact.The results obtained have been compared with other existing theoretical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…and charge transfei Because of its relative simplicity, the p t H system was often used in the past to test various models and approximations in the theory of heavy particle collisions. Consequently, a considerable amount of theoretical data is available for reactions (2) and (3) (Franco andThomas 1971, Bhadra and Ghosh 1971, Shakeshaft 1978 The presently reported close-coupled semiclassical impact parameter calculations are an extension of a n earlier work of this author (Ermolaev 1984(Ermolaev , 1990. As in the earlier work, a rectilinear trajectory was assumed for heavy particles A and B (that is where U?…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…and charge transfei Because of its relative simplicity, the p t H system was often used in the past to test various models and approximations in the theory of heavy particle collisions. Consequently, a considerable amount of theoretical data is available for reactions (2) and (3) (Franco andThomas 1971, Bhadra and Ghosh 1971, Shakeshaft 1978 The presently reported close-coupled semiclassical impact parameter calculations are an extension of a n earlier work of this author (Ermolaev 1984(Ermolaev , 1990. As in the earlier work, a rectilinear trajectory was assumed for heavy particles A and B (that is where U?…”
mentioning
confidence: 92%
“…A very good account of charge transfer is provided at low E by the impact parameter calculations of Shakeshaft (1978). However, the basis used in that work did not take the ionization channel into (1986); G, Glauber appraximatian, Franco and Thomas (1971) and Bhadra and Ghosh (1971); Sh2, close-coupled, impact parameter, symmetric two-centre AO basis, Shakeshaft (1978); 0, close-coupled, impact parameter, asymmetric two-centre AO basis, Emolaev (1990) and present calculations; 01, one-centre optical, Ast el a1 (1988); 0 2 two-centre optical, Ast el 01 (1988); Sc, one-centre, without pseudo-states, close-coupling, Schoeller el 01 (1986); R, one-and-a-half centred A 0 expansion, Reading el 01 (1981); Br, one-centre, impact parameter, with pseudo-states, Bransden el a1 (1979). (iii) Balmer alpha emission (with cascade correction).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The related rate coefficients have been taken from Capitelli et al, 22 Kossyi et al, 38 Park, 30 and Starik et al 39 Few data can be found in the literature for theses processes. When the rate coefficient is not reported in the previous references, we have used data due to Park et al, 40 Bhadra and Ghosh, 41 and Drawin 42 to derive the analytical form…”
Section: Electronic Excitation and Ionizationmentioning
confidence: 99%
“…(b) calculations of H(1s) excitation to the 3d state by incident electrons or protons (Bhadra and Ghosh 1971); (c) a demonstration (Thomas and Gerjuoy 1971) that the Glauber amplitudes for e=H( 1s) and p-H( 1s) elastic scattering or inelastic excitation marvellously can be reduced to closed form hypergeometric functions, with no further integrations necessary, thus permitting computation of the Glauber e--H(Is) and p-H(1s) collision amplitudes with hardly more effort than is required to compute the corresponding first Born approximation amplitudes ; ( d ) the even more marvellous (really miraculous) result that the total Glauber cross section for e--H( Is) elastic scattering, integrated over all electron scattering angles, can be expressed in closed form, with no further integrations necessary (Thomas and Gerjuoy 1973), thereby enabling extraction of the limiting analytic behaviour of this Glauber predicted cross section at incident energies E -+ 0 and E -+ 00 ; (e) detailed comparisons (Sheorey et al 1971) of the Glauber predictions for e--H(ls) 2s and 2p excitation with the predictions of the so-called Vainshtein approximation (Vainshtein et al 1964) ;…”
Section: 2 I Applications To Collisions With Atomic Hydrogen Targetsmentioning
confidence: 99%